Low frequency of asymptomatic carriage of toxigenic Clostridium difficile in an acute care geriatric hospital: prospective cohort study in Switzerland. Issue 1 (December 2016) - Pires, Daniela; Prendki, Virginie; Renzi, Gesuele; Fankhauser, Carolina; Sauvan, Valerie; Huttner, Benedikt; Schrenzel, Jacques; Harbarth, Stephan
Abstract Background The role of asymptomatic carriers of toxigenicClostridium difficile (TCD) in nosocomial cross-transmission remains debatable. Moreover, its relevance in the elderly has been sparsely studied. Objectives To assess asymptomatic TCD carriage in an acute care geriatric population. Methods We performed a prospective cohort study at the 296-bed geriatric hospital of the Geneva University Hospitals. We consecutively recruited all patients admitted to two 15-bed acute-care wards. Patients withC. difficile infection (CDI) or diarrhoea at admission were excluded. First bowel movement after admission and every two weeks thereafter were sampled.C. difficile toxin B gene was identified using real-time polymerase chain-reaction (BD MAXTM Cdiff). Asymptomatic TCD carriage was defined by the presence of theC. difficile toxin B gene without diarrhoea. Results A total of 102 patients were admitted between March and June 2015. Two patients were excluded. Among the 100 patients included in the study, 63 were hospitalized and 1 had CDI in the previous year, and 36 were exposed to systemic antibiotics within 90 days prior to admission. Overall, 199 stool samples were collected (median 2per patient, IQR 1-3). Asymptomatic TCD carriage was identified in two patients (2 %). Conclusions We found a low prevalence of asymptomatic TCD carriage in a geriatric population frequently exposed to antibiotics and healthcare. Our findings suggest that asymptomatic TCD carriage might contribute only marginally to nosocomial TCD cross-transmission in our and similar healthcare settings.